Development and Validation of Simultaneous Analysis of Amlodipine Besylate and Valsartan in Spiked Human Plasma Using Liquid Chromatography Tandem Mass Spectrometry - Shania Rizki Ivany; Eme Stepani Sitepu; Reynatha Pangsibidang; Yahdiana Harahap (Journal of Global Pharma Technology, 2022)
Amlodipinebesylate, a dihydropyridine calcium channel blocker, and valsartan, an angiotensin II receptor blocker, are antihypertensive agents. Fixed dose combination of amlodipine and valsartan can reduce blood pressure (BP) effectively than amlodipine or valsartan monotherapy. Amlodipine and valsartan have low concentration in blood, so a highly selective and sensitive method is required. This research is aimed to obtain an optimum and validated method for determiningamlodipinebesylate and valsartan in plasma using Liquid Chromatography Tandem Mass Spectrometry (LC-MS/MS). Mass detection was performed by Waters Xevo TQD with Electrospray Ionization source at positive ion mode in the Multiple Reaction Monitoring. Amlodipine besylate, valsartan, and irbesartan were detected at m/z409.16 > 238.06; 436.22 > 291.15; and 429.22 > 207.1; respectively. The optimum analysis condition was obtained using Waters AcquityTM UPLC C18 1.7 µm (2.1 x 100 mm); the column temperature was45oC; eluted undera gradient of mobile phase of 0.1% formic acid in water and acetonitrile at a flow rate 0.2 mL/min within 6 minutes; and irbesartan as an internal standard. Sample preparation was carried out by liquid-liquid extraction with ammonium acetate and ethyl acetate; mixed with vortex for 2 minutes; centrifugated at 2043 G-force for 10 minutes; evaporated with nitrogen gas at 50oC for 10 minutes; and reconstituted with 100 µL of mobile phase. This method fulfilled the acceptance criteria of validation based on Bioanalytical Method Validation Guidance by Food and Drug Administration in 2018. This method was linear at 0.20 – 10.00 ng/mL with r ≥ 0.997357 for amlodipine and 5.00 – 6000.00 ng/mL r ≥ 0.998476 for valsartan.